PENGARUH PEMBERIAN MINUMAN JAHE TERHADAP IBU HAMIL TRIMESTER PERTAMA DENGAN EMESIS GRAVIDARUM DI PUSKESMAS TANAH PUTIH 1 KABUPATEN ROKAN HILIR - Sitorus, Yanti Prihatin; Rahayu, Ary Oktora Sri; Susanti, Komaria; Mardiya, Rizka (Ensiklopedia of Journal, 2025)
Nausea and vomiting (emesis gravidarum) are common symptoms experienced by pregnant women in the first trimester. These symptoms require special attention because, if not properly managed, they may progress to hyperemesis gravidarum, which can affect maternal health and fetal development. This study aims to determine the effect of ginger drink consumption on first-trimester pregnant women with emesis gravidarum in the working area of Tanah Putih 1 Community Health Center. This research used a quantitative approach with a quasi-experimental design, applying a one-group pretest–posttest model. The population consisted of first-trimester pregnant women, with a sample of 15 respondents selected through purposive sampling. The research instrument was an observation sheet. The intervention was carried out over 5 days. Data were analyzed using univariate and bivariate analysis with a paired sample t-test. The univariate analysis showed that before being given ginger drinks, most first-trimester pregnant women experienced nausea and vomiting at a moderate frequency. After the intervention, nausea and vomiting remained in the moderate category but showed improvement. The bivariate analysis obtained a p-value < 0.05, indicating that ginger drinks had a significant effect in reducing nausea and vomiting during the first trimester of pregnancy. It is expected that Tanah Putih 1 Community Health Center, Rokan Hilir Regency, will improve maternal care services by applying alternative treatments to help manage emesis gravidarum in pregnant women.Keywords: Ginger drink, emesis gravidarum, first trimester pregnant women